(untitled) (Bangladesh Journal of Botany, 2015)
Seasonal change of total carbohydrate contents in samples taken from leaves and stems of almond varieties was investigated. Carbohydrate contents in the leaves and stem of all varieties showed seasonal differences. The highest carbohydrate content in the leaves and stem of all varieties was found in April, and January, respectively. The lowest carbohydrate content in the leaves of Nonpareil was found in July, that of Ferragnes and Texas in October. The lowest level of carbohydrate content in the stem of all varieties was found in July. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21677 Bangladesh J. Bot. 43(2): 223-225, 2014 (September)